2015
DOI: 10.1152/ajplung.00286.2015
|View full text |Cite
|
Sign up to set email alerts
|

ncRNA-regulated immune response and its role in inflammatory lung diseases

Abstract: Despite the greatly expanded knowledge on the regulation of immune response by protein molecules, there is increasing understanding that noncoding RNAs (ncRNAs) are also an integral component of this regulatory network. Abnormal immune response serves a central role in the initiation, progression, and exacerbation of inflammatory lung diseases, such as asthma, chronic obstructive pulmonary disease, cystic fibrosis, and acute respiratory distress syndrome/acute lung injury. Dysregulation of ncRNAs has been link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 128 publications
(204 reference statements)
0
24
0
Order By: Relevance
“…The regulation of macrophage activation has been under extensive investigation, particularly at transcriptional and epigenetic levels (1). In the past decade, it has been increasingly clear that small ncRNAs, e.g., miRs, also play a crucial role in this process (11). A number of miRs have since been found to be intrinsically involved in a variety of pathogeneses through regulating macrophage activation (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of macrophage activation has been under extensive investigation, particularly at transcriptional and epigenetic levels (1). In the past decade, it has been increasingly clear that small ncRNAs, e.g., miRs, also play a crucial role in this process (11). A number of miRs have since been found to be intrinsically involved in a variety of pathogeneses through regulating macrophage activation (11).…”
Section: Discussionmentioning
confidence: 99%
“…(ncRNAs), in these regulatory events. While there is plenty of evidence showing that small ncRNAs, such as microRNAs (miRs), participate in macrophage activation by targeting various mediators (10,11), it remains far less clear if, or how, long ncRNAs (lncRNAs) regulate this process.…”
Section: Introductionmentioning
confidence: 99%
“…Because of not coding, ncRNAs were previously known as junk RNAs. However, increasing evidence shows that ncRNAs play important regulatory roles in many biological and pathological processes, such as inflammation, viral infection, and apoptosis [6][7][8][9][10][11][12][13][14][15]. We previously reported that TGEV infection led to 21 differentially expressed miRNAs, among which miR-4331 inhibited transcription of TGEV gene7 via targeting CDCA7 [16], and miR-27b functioned as a negative regulator during TGEV-induced apoptosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…For xenograft assays, we injected 1×10 6 modi ed (sh-circRNA, sh-circRNA + miR-519 inhibitor, or sh-circRNA + SMOC2) or control PANC-1 cells subcutaneously into male nude mice (Chinese Science Academy) in the right side. We measured tumor volumes (length × width 2 × 0.5) at the indicated time points, and excised tumors 4 weeks after injection.…”
Section: Animal Studiesmentioning
confidence: 99%
“…It is already known that ncRNA contributes to a large amount of cellular RNAs, making at least 90% of human RNAs [5]. Former studies have shown that ncRNAs, like proteins, act as underlying factors in various cellular processes, including cell migration, proliferation, apoptosis, chemoresistance, angiogenesis, and the immune response [6,7]. CircRNAs are considered as essential human disease regulators as well as biomarkers in many kinds of malignancies such like PC.…”
Section: Introductionmentioning
confidence: 99%